Adapt or Die: Targeting Unique Transmission-Stage Biology for Malaria Elimination - van der Watt, Mariëtte E.; Reader, Janette; Birkholtz, Lyn-Marié (Frontiers in Cellular and Infection Microbiology, 2022)
Plasmodium parasites have a complex life cycle that includes development in the human host as well as the Anopheles vector. Successful transmission of the parasite between its host and vector therefore requires the parasite to balance its investments in asexual replication and sexual reproduction, varying the frequency of sexual commitment to persist within the human host and generate future opportunities for transmission. The transmission window is extended further by the ability of stage V gametocytes to circulate in peripheral blood for weeks, whereas immature stage I to IV gametocytes sequester in the bone marrow and spleen until final maturation. Due to the low gametocyte numbers in blood circulation and with the ease of targeting such life cycle bottlenecks, transmission represents an efficient target for therapeutic intervention. The biological process of Plasmodium transmission is a multistage, multifaceted process and the past decade has seen a much deeper understanding of the molecular mechanisms and regulators involved. Clearly, specific and divergent processes are used during transmission compared to asexual proliferation, which both poses challenges but also opportunities for discovery of transmission-blocking antimalarials. This review therefore presents an update of our molecular understanding of gametocyte and gamete biology as well as the status of transmission-blocking activities of current antimalarials and lead development compounds. By defining the biological components associated with transmission, considerations for the development of new transmission-blocking drugs to target such untapped but unique biology is suggested as an important, main driver for transmission-blocking drug discovery.